Students’ Beliefs towards Online Assessments: Applying Technology Acceptance Model - Widiatmoko, Paulus; Endarto, Ignatius Tri ((JELE) Journal Of English Language and Education, 2022)
The pivotal role of ICT during Covid19 pandemic has been indisputable, including the shift from conventional modes of assessment. Pre-service teacher education, therefore, needs to prepare students’ proficiency to design and conduct various types of tests and assessments. This study was aimed to investigate future teachers’ beliefs on online assessments and their intention to use them. Investigation on the students’ perception towards these modes of assessment as compared with the conventional ones was further conducted. Qualitative data analysis resulted in general acceptance of online assessments with variations of beliefs. Meanwhile, participants’ computer self-efficacy and intention to use online assessment were found out to gain the highest mean score. Furthermore, Path Analysis demonstrated strong causal relationship of most factors in the model, except on the frequency of use. This study concluded the reliability of Technology Acceptance Model (TAM) as a framework to investigate pre-service teachers’ acceptance of online assessments for language instruction. Moreover, student belief system should be catered in the enactment of instructional technology, especially in a teacher training program.